Fungal-Type Terpene Synthases in Marchantia polymorpha Are Involved in Sesquiterpene Biosynthesis in Oil Body Cells. (13th January 2021) - Takizawa, Ryosuke; Hatada, Miki; Moriwaki, Yuta; Abe, Sachika; Yamashita, Yuko; Arimitsu, Ryoma; Yamato, Katsuyuki T; Nishihama, Ryuichi; Kohchi, Takayuki; Koeduka, Takao; Chen, Feng; Matsui, Kenji
Abstract: The liverwort Marchantia polymorpha possesses oil bodies in idioblastic oil body cells scattered in its thallus. Oil bodies are subcellular organelles in which specific sesquiterpenes and bisbibenzyls are accumulated. Therefore, a specialized system for the biosynthesis and accumulation of these defense compounds specifically in oil bodies has been implied. A recent study on M. polymorpha genome sequencing revealed 10 genes that shared high similarities with fungal-type terpene synthases (TPSs). Eight of these fungal-type TPS-like genes in M. polymorpha ( MpFTPSL1-6, -9 and -10 ) are located within a 376-kb stretch on chromosome 6 and share similarities of over 94% at the nucleotide level. Therefore, these genes have likely originated from recent gene duplication events. The expression of a subset of Mp FTPSL s was induced under non-axenic growth on vermiculite, which increased the amounts of sesquiterpenes and number of oil bodies. The tdTomato fluorescent protein-based in-fusion reporter assay with Mp FTPSL2 promoter revealed fluorescent signals specifically in oil body cells of the thallus, indicating that Mp FTPSL2 functions in oil body cells. Recombinant MpFTPSL2 expression in Escherichia coli led to sesquiterpene synthesis from farnesyl pyrophosphate. Moreover, suppression of a subset of Mp FTPSL s through RNA interference reduced sesquiterpene accumulation in thalli grown on vermiculite. Taken together, these results suggest that at least a subset of Mp FTPSL s is involved in sesquiterpene synthesis in oil body cells.